Validation and comparison of instruments to identify frail patientes in primary care settings: Study protocol - Vergara, Itziar; Rivas-Ruiz, Francisco; Vrotsou, Kalliopi; Contreras-Fernández, Eugenio; Téllez-Santana, Teresa; Machón, Monica; Díez Ruiz, Ana Isabel; de Mesa Berenguer, Yolanda; Bueno, Andoni; et al (BMC Springer Nature, 2016)
Background: In the last few years several indices and tools, aimed at identifying frail subjects in various care settings have been developed. However, to date none of them has been incorporated into usual practice in the primary care setting. The purposes of this study are: 1) to evaluate the predictive capacity of the Tilburg Frailty Indicator (TFI), the Gérontopôle Frailty Screening Tool (GFST) and the KoS model together with two biomarker levels (SOX2 and p16INK4a) for adverse events related to frailty; 2) to determine differences in the use of healthcare services according to frailty. Methods/design: Prospective multicentre cohort study with a 2-year follow-up. The study will be performed in primary care centres of Gipuzkoa and Costa del Sol, both located in Spain. Autonomous, non-institutionalized individuals aged 70 and over that agree to participate in this study will constitute the study population. A total of 900 individuals will be randomly selected from the healthcare administrative data bases of the participating health services. Data will be collected at baseline and at 1 and 2 years. The main independent variables assessed at baseline will be TFI outcomes, GFST and the KoS model, together with the expression of SOX2 and p16INK4a levels. During follow-up, loss of autonomy, the occurrence of death and consumption of healthcare resources will be assessed. Discussion: The main focus of this work is the identification and evaluation of several instruments constructed under different rationales to identify frail subjects in primary care settings. The resulting outcomes have potential for direct application to the primary care practice. Early identification of the onset of functional impairment of elderly is an essential, still unresolved aspect in the prevention of dependence in the scope of primary care.
Keywords: Atención primaria; Frailty; Identification tools; Primary care